The Role of Traditional Stove-Base in Indonesia’s Vernacular Architecture: Lessons from Kampung Naga - Febri Fahmi Hakim; Dwi Siswi Hariyani; Eugenius Pradipto (Universitas Sebelas Maret Surakarta, 2025)
The study of the stove as part or element of a vernacular architecture in the literature is more widely discussed regarding cultural aspects and practical uses. This study aims to examine to what extent considerations of micro-climate and building physics are applied by the indigenous people of Kampung Naga in the configuration of the cooking stove in their houses. We select a simulation research design as the primary method of analysis. We use the Ansys Student 2025 R1 version to conduct 2D Fluent flow and 2D heat transfer simulations. The findings confirmed that the traditional stove of the Kampung Naga community which consists of Hawu and Parako reflects a genius design consideration by the local people which shows its capability to control the buoyancy-driven natural convection and heat distribution in the two burners of the stove as well as preventing the heat from affecting the surrounding wooden and bamboo materials.